Conflicting Readings of the Brutality of Late Communism - The Case of the Slovo Patsana Series - Miša Đurković (Etnoantropološki Problemi)
The paper explores how a phenomenon of popular culture undergoes very different interpretations within the same cultural circle. The author focuses on the immensely popular Russian series Boy’s Word, which premiered in 2023. The show deals with the phenomenon of juvenile criminal gangs in Kazan, involving many associations and layers. All this was reinforced by the framework of the Ukrainian war, and the absurd outcome that it is the most watched series in Ukraine even though it is banned.